2019
DOI: 10.1016/j.eats.2019.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Tenodesis of the Long Head Biceps Tendon Using a Double Lasso-Loop Suture Anchor Configuration

Abstract: Multiple different techniques exist for performing a biceps tenodesis, and the literature has yet to define a particular technique as superior with respect to outcomes. Factors as the center of various clinical and biomechanical studies include analyzing arthroscopic versus open techniques, optimal fixation sites, and the use specific fixation devices (i.e., anchor, screw). This article details an all-arthroscopic approach for proximal tenodesis of the long head of the biceps tendon (LHBT) using a 2-portal met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Several other all-arthroscopic biceps tenodesis techniques have been described. 1,9,10 The first technique utilizes a transtendinous all-suture anchor with a suture wrap technique to secure the tendon for fixation. 10 Compared with the Loop 'n' Tack, this technique is similar in that operative time is reduced, but the wrapping suture technique requires knot tying over the long head of the biceps (LHB) tendon, which can lead to irritation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other all-arthroscopic biceps tenodesis techniques have been described. 1,9,10 The first technique utilizes a transtendinous all-suture anchor with a suture wrap technique to secure the tendon for fixation. 10 Compared with the Loop 'n' Tack, this technique is similar in that operative time is reduced, but the wrapping suture technique requires knot tying over the long head of the biceps (LHB) tendon, which can lead to irritation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Theoretical advantages include multiple points of fixation, but this technique leads to increased operative time and carries a risk of overtensioning. 1 The Loop 'n' Tack stitch helps to avoid this, as its simple technique helps to decrease operative time, and its use of 1 free suture end for fixation assists in tensioning. The mode-of-failure analysis did demonstrate different mechanisms of failure when comparing the Loop 'n' Tack configuration with the double half-racking and Krakow stitch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroscopic suprapectoral biceps tenodesis has distinct advantages including minimal soft tissue dissection, less scar formation, lack of need of an assistant for soft tissue retraction compared to open subpectoral biceps tenodesis [12]. When tenodesis is performed, many different factors affect tendon repair including tendon quality and strength of the stitch.…”
Section: Introductionmentioning
confidence: 99%
“…For improving strength, Laffoseet al introduced a new technique named Lasso stitch in 2006 [13], which showed superior biomechanical properties against load to failure compared to compressive rivet and interference screw [14]. Some authors also stated that the Lasso loop technique has less humeral fracture risk theoretically associated with drilling than interference screw [12].…”
Section: Introductionmentioning
confidence: 99%